Pengaruh Gerakan Literasi Sekolah Terhadap Minat Menulis Siswa Sekolah Dasar - Dewi Ariyani; Syifa Qolbiyulia; Puji Nur Aisyah; Ikhda Nani Nasikhatun; Mohammad Fadlil Asshidiq (Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
This study aimed to investigate the effect of the School Literacy Movement on students' interest in writing at SD Negeri 7 Ciamis throughout the 2019-2020 academic year. The quantitative methodology of ex-post facto research was utilized for this study. There are two factors in this study: the School Literacy Movement (X) and writing interest (Y). This study's population consisted of sixth-grade pupils from SD Negeri 7 Ciamis, with a sample size of 30 individuals. The sampling method employed was a random sample. Using a Likert scale, information was gathered via a questionnaire. Normality and linearity tests are utilized to evaluate the data analysis requirements. The Pearson product moment correlation method is utilized as the data analysis technique. The results of the study indicate that the School Literacy Movement had no influence on the students of SD Negeri 7 Ciamis' interest in writing. This is evidenced by the r value of 0.210 r table 0.361 for the association between the School Literacy Movement (X) and writing interest (Y). The significance value used in the r table is 5%. The estimated r value is less than the r table, indicating that there is no association or correlation between the variable School Literacy Movement (X) and the variable interest in writing (Y).